Peningkatan Kualitas Manajemen Keuangan UMKM Melalui Pelatihan Pencatatan Sederhana Di Desa Banyuresmi, Sukahening, Tasikmalaya - Rika Mustika; Tri Rizki Maisa; Putri Nuer Asiah; Fathiyyah Nurauliya Fitri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Simple financial statements are used to make it easier for MSME actors to manage their businesses. This is a strategy used as an effort to realize neat business management by implementing a financial recording system. Financial information has such an important influence in order to achieve business success, even for small and medium entrepreneurs. Many business actors do not have literacy about financial management and there are also many business actors who do not fully understand the importance of managing capital and income properly. Especially what happened in Banyuresmi Village, Sukahening District. Many MSME actors still do not know how to make a simple financial recording system to maximize profits in their business. The purpose of this study is to introduce the use of financial management to MSMEs so that they can support the progress of MSMEs, especially in terms of finance. At the same time, it is an effort to educate the community of MSME actors in Banyuresmi Village. The method of implementing this KKM activity is by holding training directly by inviting 25 MSME actors in Banyuresmi Village. The research method used in this study is a qualitative method using a descriptive approach by utilizing secondary data from various literature, such as journals/articles and pages.